Simulation of WirelessHART networked control system with packet dropout - Chung, T.D. (Institute of Electrical and Electronics Engineers Inc., 2015)
Industrial communication standard like WirelessHART enables wireless control in process plants. This paper presents a study on wired and wireless networked control system. It emphasizes on using packet dropout array for Markov chain simulation of packet dropout process, a key parameter affecting plant's performance, in a closed-loop WirelessHART networked control system. Additionally, Bernoulli simulation of the process is covered for comparison purpose. Overshoot was found to be 633.3 for Bernoulli model, 33.9 for Markov model and even through it is the major drawback of the system, WirelessHART networked control system is still suitable for control applications when non-time-critical plant has response time longer than sampling period thousands times even with 50 , 40 dropout probabilities for Bernoulli, Markov models. Â© 2015 IEEE.